African Ancestry Gradient Is Associated with Lower Systemic F2-Isoprostane Levels. (31st January 2017) - Annor, Francis; Goodman, Michael; Thyagarajan, Bharat; Okosun, Ike; Doumatey, Ayo; Gower, Barbara A.; Il'yasova, Dora
Abstract : Context . Low levels of systemic F2 -isoprostanes (F2 -IsoP) increase the risk of diabetes and weight gain and were found in African Americans. Low F2 -IsoPs could reflect an unfavorable metabolic characteristic, namely, slow mitochondrial metabolism in individuals with African ancestry. Objective . To examine differences in plasma F2 -IsoPs in three groups with a priori different proportion of African ancestry: non-Hispanic Whites (NHWs), US-born African Americans (AAs), and West African immigrants (WAI). Design . Cross-sectional study. Setting . Georgia residents recruited from church communities. Participants . 218 males and females 25–74 years of age, who are self-identified as NHW (n = 83 ), AA (n = 56 ), or WAI (n = 79 ). Main Outcome Measure(s) . Plasma F2 -IsoPs quantified by gas chromatography-mass spectrometry. Results . After adjustment for age, gender, obesity, and other comorbidities, WAI had lower levels of plasma F2 -IsoP than AA (beta-coefficient = −9.8, p < 0.001 ) and AA had lower levels than NHW (beta-coefficient = −30.3, p < 0.001 ). Similarly, among healthy nonobese participants, F2 -IsoP levels were lowest among WAI, followed by AA, and the highest levels were among NHW. Conclusion . Plasma F2 -IsoPs are inversely associated with African ancestry gradient. Additional studies are required to test whether optimization of systemic F2 -IsoP levels can serve as means to improve race-specific lifestyle and pharmacological intervention targeted to obesity prevention and treatment.